Assessing the understanding and practices of 3R's among the secondary school students - Embong, A.M. (2013)
Indulging the values towards sustainable environment has become the main priority in the National Philosophy of Education and being incorporated into the Malaysia Education Curriculum. Students are taught to appreciate the earth and its natural sources at a young age through various activities. A study was taken place to gauge the environmental education pertaining the understanding and practices of 3R's among secondary school students from five states in Malaysia. Data was collected from 468 students ranging from 13 to 19 years old using a survey questionnaire. It involved the major races in Malaysia from both genders. The results showed that students have a good understanding on 3R's with the most understanding on the Recycle followed by Reuse and Reduce. Urban students understood Reuse the most as compared to rural students who understood Recycle the most. They were also aware of the benefits gained from 3R's. In terms of sustainable behavior, students from both areas practiced the 3R's weekly and monthly. Some main statements regarding the practice of 3R's were obtained from students. The results also showed that schools were the main source to 3R's followed by electronic and printed media. Â© 2013 IEEE.